2009
DOI: 10.1145/1647300.1658422
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Power Efficiency with Asymmetric Multicore Systems

Abstract: In computing systems, a CPU is usually one of the largest consumers of energy. For this reason, reducing CPU power consumption has been a hot topic in the past few years in both the academic community and the industry. In the quest to create more power-efficient CPUs, several researchers have proposed an asymmetric multicore architecture that promises to save a significant amount of power while delivering similar performance to conventional symmetric multicore processors. An AMP (asymmetric multicore processor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…O potencial dos processadores assimétricos em economizar energia foi apresentado em [6] através de implementação de estratégias para escalonamento ciente da assimetria do processador usando algoritmos que podem ser aplicados em sistemas reais e usados nos processadores heterogêneos ou assimétricos, sem sobrecarga significativa. O gerenciamento dinâmico de energia foi desenvolvido para reconfigurar dinamicamente o sistema e assim fornecer os serviços solicitados e os níveis de desempenho com um número mínimo de componentes ativos ou uma carga mínima em tais componentes [3].…”
Section: Trabalhos Relacionadosunclassified
“…O potencial dos processadores assimétricos em economizar energia foi apresentado em [6] através de implementação de estratégias para escalonamento ciente da assimetria do processador usando algoritmos que podem ser aplicados em sistemas reais e usados nos processadores heterogêneos ou assimétricos, sem sobrecarga significativa. O gerenciamento dinâmico de energia foi desenvolvido para reconfigurar dinamicamente o sistema e assim fornecer os serviços solicitados e os níveis de desempenho com um número mínimo de componentes ativos ou uma carga mínima em tais componentes [3].…”
Section: Trabalhos Relacionadosunclassified
“…Like in other heterogeneous systems, load balancing and scheduling are fundamental challenges that must be addressed to effectively exploit all the resources in AMC platforms [8,9,10,11,12,13]. Mobile applications rely on multi-programmed workloads to balance the load in the system, while supercomputer applications rely on hand-tuned code to extract maximum performance.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work [5,10,32,54,55,60,62,96,97,97,98,100,104,106,111] on optimizing the performance and power efficiency of execution on heterogeneous architectures, regardless of their ISA interface, has shown that the mapping of heterogeneous resources to programs is crucial. Specifically, heterogeneous resources should be allocated to those programs which make the most of their acceleration potential.…”
Section: Contributionmentioning
confidence: 99%
“…In single-ISA systems performance asymmetry comes from variation of ISA-transparent characteristics, and typically consist of few powerful, large area cores and many smaller and power-efficient cores [60,62]. Single-ISA performance asymmetry is most frequently emulated by varying core clock frequency, preserving software binary compatibility [32,97,98,100]. Shared-ISA architectures extend micro-architectural, single-ISA asymmetry with functional asymmetry: all cores implement a common, basic ISA while few of them extend it with accelerating instructions for executing certain operations accelerated.…”
Section: Other Dynamic Scheduling Solutions For Asymmetric Platformsmentioning
confidence: 99%
See 1 more Smart Citation